Education Using Booklet Media Increases Pregnant Women's Knowledge about Healthy Eating Patterns: Edukasi Menggunakan Media Booklet Meningkatkan Pengetahuan Ibu Hamil tentang Pola Makan Sehat - Kusika, Sri Yanti; Khotimah, Nurul; Maineny, Arie; Silfia, Niluh Nita; Hadriani (Poltekkes Kemenkes Palu, 2024)
Background: The diet of pregnant women and low knowledge of pregnant women about nutrition can cause pregnant women to experience chronic energy deficiency (CED). Data on cases of pregnant women with CED at the Sangurara Community Health Center were 36 people from January to May 2023. Objective: It is known the influence of education using booklet media about eating patterns on the knowledge of pregnant women Method: The research design is pre-experimental with a one group pretest - posttest design. The sampling technique was determined by total sampling, namely 36 KEK pregnant women. The research instrument is a questionnaire. Data analysis used the Wilcoxon test. Results: Before treatment, the majority (63.9%) had poor knowledge and afterward as many as (66.7%) had good knowledge. The results of the data analysis have a sig (2-tailed) value: 0.000, so Ho is rejected. Conclusion: education using booklet media increases pregnant women's knowledge about healthy eating patterns in the Sangurara Community Health Center Working Area. It is recommended that the booklet be used by health workers as an educational instrument for pregnant women to prevent KEK